Infinitude of Pride p such that ap+b is prime where a, b are coprime integers - Bado (My University, 2019)
In 1904, Dickson [6] stated a very important conjecture. Now people call it Dickson’s conjecture. In 1958, Schinzel and Sierpinski [3] generalized Dickson’s conjecture to the higher order integral polynomial case. However, they did not generalize Dickson’s conjecture to the multivariable case. In 2006, Green and Tao [9] considered Dickson’s conjecture in the multivariable case and gave directly a generalized Hardy-Littlewood estimation. But, the precise Dickson’s conjecture in the multivariable case does not seem to have been formulated. In this paper, based on the idea in [8] we introduce an interesting class of prime numbers to solve the dickson conjecture Although this article does not solve the dickson conjecture but it solves a problem that is similar to the Dickson conjecture. the problem is stated as follows being given two coprime integers a, b there is an infinity of prime numbers p such that ap+b is prime. This type of prime numbers we call it Bado-Tiemoko prime numbers .
Keywords: Infinitude; Prime